If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)(y + 8) = 0 Reorder the terms: (6 + x)(y + 8) = 0 Reorder the terms: (6 + x)(8 + y) = 0 Multiply (6 + x) * (8 + y) (6(8 + y) + x(8 + y)) = 0 ((8 * 6 + y * 6) + x(8 + y)) = 0 ((48 + 6y) + x(8 + y)) = 0 (48 + 6y + (8 * x + y * x)) = 0 (48 + 6y + (8x + xy)) = 0 Reorder the terms: (48 + 8x + xy + 6y) = 0 (48 + 8x + xy + 6y) = 0 Solving 48 + 8x + xy + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + 8x + xy + -48 + 6y = 0 + -48 Reorder the terms: 48 + -48 + 8x + xy + 6y = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 8x + xy + 6y = 0 + -48 8x + xy + 6y = 0 + -48 Combine like terms: 0 + -48 = -48 8x + xy + 6y = -48 Add '-6y' to each side of the equation. 8x + xy + 6y + -6y = -48 + -6y Combine like terms: 6y + -6y = 0 8x + xy + 0 = -48 + -6y 8x + xy = -48 + -6y Reorder the terms: 48 + 8x + xy + 6y = -48 + -6y + 48 + 6y Reorder the terms: 48 + 8x + xy + 6y = -48 + 48 + -6y + 6y Combine like terms: -48 + 48 = 0 48 + 8x + xy + 6y = 0 + -6y + 6y 48 + 8x + xy + 6y = -6y + 6y Combine like terms: -6y + 6y = 0 48 + 8x + xy + 6y = 0 The solution to this equation could not be determined.
| 5(2p+10)=10(p+2)-40 | | 9(x+6y)+9(4x+5y)= | | (-6xy)(8xy)= | | ln(y)=0.63 | | 5z^5q^2+2z^5q= | | 2.1(3+4x)-8.1=1.5(2+4x) | | 16.4+0.5x=9.4-1.1x+12 | | .70x+.05(8-x)=.10(121) | | -0.5-3=12 | | =16-14-13-18+19+14-17+21 | | 0.3(c+5)-0.7(c+1)=6 | | 30(x-0.8)=10x+16 | | 16.4+0.5x=9.4-1.1+12 | | p=-x^2+10x+35 | | 3(2a-7)+4=-5 | | 0.45*5p=29.25 | | 2x^2*35x*-7.5=0 | | 1y+27=y+12 | | 2a+6=2(6a+13) | | 2p^2=-7p-3 | | 35t=420 | | 2a+6=2(0.6a+1.3) | | =14-12-21-14+17-18+19-32 | | 4.1+8.3=41.264 | | x-0.33=0.66 | | 4x-3+x=12 | | 7(2x+9)=3x+28 | | 4s-12=4s-12 | | 0=t^3-9t+2 | | 2.5(x-2)= | | 00.6(y-15)=0.06y+0.05 | | =-86(49+(-48)) |